1985
DOI: 10.1177/014107688507800804
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Recurrent Spontaneous Abortions by Leukocyte Transfusions

Abstract: One hundred and thirty-nine couples referred because of recurrent abortions with no obvious cause were assessed for genetic similarity using the HLA major histocompatibility system. Comparison with 103 fertile control couples demonstrated that a much higher proportion of couples in the abortion group shared two or more HLA antigens. Using this criterion, 44 wives out of the 139 couples referred, when compared with a child-bearing group, appeared to share a greater than expected number of histocompatibility ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 22 publications
0
26
1
2
Order By: Relevance
“…There is increasing evidence that some recurrent abortions in women might be preventable by immunization of the mother against paternal or third party alloantigens (Taylor & Faulk, 1981;Mowbray et ai, 1985). Ethical concerns limit the extent of studies on this subject in women but there now exist several models of pregnancy failure in mice and its correction by lymphocyte alloimmunization.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that some recurrent abortions in women might be preventable by immunization of the mother against paternal or third party alloantigens (Taylor & Faulk, 1981;Mowbray et ai, 1985). Ethical concerns limit the extent of studies on this subject in women but there now exist several models of pregnancy failure in mice and its correction by lymphocyte alloimmunization.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of unexplained recurrent spon taneous abortion (RSA) ranges from psycho therapy to aggressive immunotherapeutic in tervention [1], The practice of immunother apy remains controversial despite widespread use during the past 10 years [2][3][4], Immuniza tion of RSA patients with paternal [5] or third-party [6] leukocytes is an approach used for patients who fail to manifest adequate immune recognition of paternally inherited fetal antigens. This hyporeactivity is thought to be due to a lack of recognition of a group of cell surface molecules called trophoblast-lymphocvte cross-reactive (TLX) alloantigens [7]. '…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy using paternal lymphocytes and its beneficial effects on RPL have been discussed for decades. Through these debates, immunization with both paternal lymphocyte [57,58] and pooled allogeneic lymphocytes [59,60] have apparently improved the successful pregnancy rate; in one double-blind controlled study, a significant increase in successful pregnancy outcomes was reported among women who had been immunized with their husband's cells compared w ith women who had received autologous lymphocytes [58]. These early studies in the 1980s were subsequently confirmed by multicenter studies [61][62].…”
Section: Cd3mentioning
confidence: 99%